PENGARUH JANGKA WAKTU PINJAMAN, PERINGKAT KREDIT DAN TUJUAN PINJAMAN TERHADAP KEPUTUSAN PEMBIAYAAN DENGAN INTERVENING JUMLAH PINJAMAN - Ilmiddaviq, Muhammad Bahril (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2020)
Most of the UMKM have difficulty in obtaining business loans from banks or other financial institutions as business capital for them. Capital problems are a classic problem for them, even capital constraints can be a factor causing business failure. the issue of trust is the main measure for creditors to extend credit. Trust has an important role in understanding economic growth, financial development, low capital market participation, low diversification of financial investors' portfolios. Seeing this condition, ?PT. Permodalan Nasional Madani (Persero)? Unit Layanan Modal Mikro or abbreviated as PNM ULAM began to look and allocate credit to the UMKM sector. This research method uses path analysis models using binary logistics. The object in this study is customers who are domiciled in the Mojokerto regency at PT.Pododalan Nasional Madani (Persero) recorded in the 2018 fiscal year and engaged in the UMKM sector as many as 42 customers. From the data processing and discussion as described above it can be concluded that the variable loan term, credit rating, loan objectives do not directly influence the financing decision. Whereas with the intervening variable the amount of financing is only the credit rating which indirectly influences the financing decision. the indirect effect of the credit rating of 3,804 points.